Inhibitors of NLRP3 Inflammasome in Ischemic Heart Disease: Focus on Functional and Redox Aspects - Pasquale Pagliaro; Claudia Penna (MDPI AG, 2023)
Myocardial ischemia-reperfusion injury (MIRI) is caused by several mechanisms, including the production of reactive oxygen species (ROS), altered cellular osmolarity, and inflammatory response. Calcium overload, altered oxygen levels, and mitochondrial ROS are also involved in these MIRI processes, resulting in the irreversible opening of the mitochondrial permeability transition pore (mPTP). These mechanisms and processes are associated with NLRP3 inflammasome priming and activation, which can also induce cell death by pyroptosis through the up-regulation of the caspase-1 pathway and IL-18 release. In addition, endothelial dysfunction, both in the presence and absence of MIRI, is also accompanied by altered oxygen levels, decreased nitric oxide production, and ROS overproduction, resulting in the expression of adhesion molecules and leukocyte infiltration in which the NLRP3 inflammasome plays a central role, thus contributing, through endothelial dysfunction, to the alteration of coronary flow, typical of ischemic heart disease. Given the intricate interrelationship between ROS and NLRP3, ROS inhibitors can reduce NLRP3 inflammasome activation, while NLRP3 inhibitors can reduce oxidative stress and inflammation. NLRP3 inhibitors have been intensively studied as anti-inflammatory agents in basic cardiovascular sciences. In this review, we analyze the interrelation between ROS and NLRP3 in ischemic heart disease and the effects of some NLRP3 inhibitors as possible therapeutic agents in this disease condition. All compounds considered in this review need larger studies to confirm their appropriate use in clinical scenarios as anti-ischemic drugs.